Climatic change drives dynamic source–sink relationships in marine species with high dispersal potential. Issue 6 (16th February 2021) - Silva, Catarina N. S.; Young, Emma F.; Murphy, Nicholas P.; Bell, James J.; Green, Bridget S.; Morley, Simon A.; Duhamel, Guy; Cockcroft, Andrew C.; Strugnell, Jan M.
Abstract: While there is now strong evidence that many factors can shape dispersal, the mechanisms influencing connectivity patterns are species‐specific and remain largely unknown for many species with a high dispersal potential. The rock lobsters Jasus tristani and Jasus paulensis have a long pelagic larval duration (up to 20 months) and inhabit seamounts and islands in the southern Atlantic and Indian Oceans, respectively. We used a multidisciplinary approach to assess the genetic relationships between J. tristani and J. paulensis, investigate historic and contemporary gene flow, and inform fisheries management. Using 17, 256 neutral single nucleotide polymorphisms we found low but significant genetic differentiation. We show that patterns of connectivity changed over time in accordance with climatic fluctuations. Historic migration estimates showed stronger connectivity from the Indian to the Atlantic Ocean (influenced by the Agulhas Leakage). In contrast, the individual‐based model coupled with contemporary migration estimates inferred from genetic data showed stronger inter‐ocean connectivity in the opposite direction from the Atlantic to the Indian Ocean driven by the Subtropical Front. We suggest that the J. tristani and J. paulensis historical distribution might have extended further north (when water temperatures were lower) resulting in larval dispersal between the ocean basis being more influenced by the Agulhas Leakage than the Subtropical Front. As water temperatures in the region increase in accordance with anthropogenic climate change, a southern shift in the distribution range of J. tristani and J. paulensis could further reduce larval transport from the Indian to the Atlantic Ocean, adding complexity to fisheries management. Abstract : Using a multidisciplinary approach combining genetic data (SNPs) with individual‐based modelling, we show that patterns of connectivity between rock lobsters Jasus tristani and Jasus paulensis changed over time in accordance with climatic fluctuations. Historical connectivity between the ocean basis was more influenced by the Agulhas Leakage (from the Indian to the Atlantic Ocean) while contemporary connectivity is stronger in the opposite direction from the Atlantic to the Indian Ocean, driven by the Subtropical Front.